Analisis Manajemen Perubahan dalam Sistem Ekonomi Syariah terhadap Perubahan Kinerja Organisasi di Kapasitas Kepemimpinan : Studi Kasus PT Semen Indonesia - Nuri Aslami; Rofiqoh Hannum Rao (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Cement is a building material commodity that has an important role in the smooth running of development, especially in the construction sector. The purpose of this study is to find out how the influence of Change Management in the Islamic economic system on Company Organizational Performance and to find out the Organizational Performance and Organizational Performance Aspects that have a major influence based on Analytic Network Process analysis. Respondents involved in this study were a research analyst and a business owner with a material store business unit. The sampling technique used in this research is purposive sampling method. This research is a descriptive research and requires models and analytical tools that are able to accommodate this research. The analytical tool used in this study is the Analytic Network Process (ANP) method. With ANP, this study analyzes the value per cluster, the value of all nodes, and the value of change management cluster synthesis. The results of the study show that change management in Islamic economics has an impact on organizational performance. In change management, leadership performance is one of the six dimensions that has the most important impact and gets the highest score. If we look at Islamic Economics, an economy that underlies it in its fair implementation, is more in favor of the people's economy. While on organizational performance, task performance gets the highest score.